Pembenihan Selektif Kerapu Bebek, Cromileptes altivelis Turunan ke-2 (F-2) - Tridjoko, Tridjoko; Haryanti, Haryanti; Muzaki, Ahmad; Sutarmat, Tatam (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The aim of this experiment was to know the gonad development of humpback grouper Cromileptes altivelis F-2 progeny. The F-2 progeny fishes were produced from selective breeding and composed by Lot 1, Lot 2 and Lot 3. The fishes were reared in the cylinder concrete tanks containing 75 m³, 10 m³ water and floating cages. Fishes were fed with commercial dry pellet in addition with vitamin mix, vitamin C and vitamin E. The result indicated that the mature gonad female of F-2 grouper broodstocks have been achieved. The female broodstocks with 590 g weight produced oocytes with diameter more than 400 µm. Genetic analysis showed that grouper Lot 2 was homogenous, did not find any polymorphism among individual fish, however Lot 1 and Lot 3 still showed high heterozygocity as 0.18 and 0.58, respectively.